COVID-19 and Multilateralism - Sachs, Jeffrey (Consilience, 2020)
The world faces its greatest crisis since World War II and its greatest economic calamity since the Great Depression. History shows two ways out of a global crisis: a global leader that guides an effective response—and helps to pay for it—or global cooperation through the UN multilateral framework. Alas, we have no global leader today. The United States today is more a force of destruction than a leader. Our only way forward is cooperation under the UN mandate. Let me explain.